Digital transformation through electronic-based government system performance as public relations strategy - Fardiah, Dedeh; Darmawan, Ferry; Rinawati, Rini; Supaat, Viky Edya Martina; Hadnansyah, Edwan (Universitas Padjadjaran, 2024)
Background: West Java Province is advancing towards digital governance with the West Java Digital Service. In 2023, it received the Indonesian Regional Government Appreciation Award for Integrated Digital Transformation from B-Universe. The revamped jabarprov.go.id portal provides an integrated one-stop public service platform, enhancing public access to information and services. Integration across regional, district, and city agencies has simplified portal management. The government’s approach to digital transformation includes adopting an electronic-based government system (SPBE) as part of its public communication strategy. This study explores the effectiveness of digital transformation via SPBE for communication advancement by the West Java Regional Government. It assesses its impact on public accessibility and service efficiency. Methods: This study uses a case study method and Focus Group Discussions with E-government managers in 28 cities/regencies in West Java. Results: The study reveals that public communication encompasses services for society, businesses, government, and ASN. Interaction processes involve infrastructure development, information provision, two-way interaction, and managing feedback. Information transactions include a complaint platform, guidelines, complaint submission, verification, handling, confirmation, resolution, and evaluation. Collaborations span government, society, the private sector, NGOs, academia, and international partners. Public communication optimation improves satisfaction, efficiency, transparency, accountability, and participation. Conclusion: Digital transformation through SPBE enhances efficiency, transparency, and public involvement, with government public relations crucial for supporting and optimizing SPBE performance. Implication: The research implies that the government should enhance information models for broader accessibility, which covers those with physical or digital limitations, and facilitate two-way interactions through digital platforms, AI, and Chatbots. Besides, education and socialization regarding SPBE services are fundamental.